Kill&Repel Coatings: The Marriage of Antifouling and Bactericidal Properties to Mitigate and Treat Wound Infections (Adv. Funct. Mater. 9/2022). (23rd February 2022) - Garay‐Sarmiento, Manuela; Witzdam, Lena; Vorobii, Mariia; Simons, Christian; Herrmann, Niklas; de los Santos Pereira, Andres; Heine, Elisabeth; El‐Awaad, Islam; Lütticken, Rudolf; Jakob, Felix; Schwaneberg, Ulrich; Rodriguez‐Emmenegger, Cesar
Abstract : Wound Dressings In article number 2106656, Ulrich Schwaneberg, Cesar Rodriguez‐Emmenegger, and co‐workers present a novel antimicrobial coating for wound dressings, termed the Kill&Repel strategy. The bactericidal action of the coating, synergistically combined with antifouling properties and biocompatibility, enables wound protection and treatment against bacterial pathogens, far superior to that of commercial dressings. Moreover, the Kill&Repel coating is readily applicable without any strenuous procedures, holding promise for clinical application.